Nurses’ Perspectives on Spirituality and Spiritual Care for Critically Ill Patients in Intensive Care Units: A Systematic Review of Qualitative Studies - Nour Dhiaeyah Binti Supuan Zaki; Soh Kim Lam; Ahmad Aizuddin Bin Md Rami (Africa Journal of Nursing and Midwifery, 2026)
Background: Nurses’ competencies in spiritual care are increasingly in demand in intensive care (ICU) units, yet their perspectives, preparedness and challenges in delivering such care remain unclear.Aim: This qualitative systematic review explores ICU nurses’ understanding and perspectives of spiritual care for critically ill patients.Method/Study Design: Following the Enhancing Transparency in Reporting the Synthesis of Qualitative Research guidelines, eligible qualitative and mixed-method studies (2016–2025) were included, appraised using the Critical Appraisal Skills Programme checklist and synthesised using meta-aggregation.Results: Fifteen studies generated seven themes on nurses’ understanding, practices, barriers and facilitators, benefits and strategies for improving spiritual care. Sub-themes addressed individual, patient, family and workplace factors.Conclusion: Nurses’ competencies and delivery of spiritual care need to be enhanced in order to translate the benefits from theory to practice, particularly in critically ill patients.Relevance to Clinical Practice: Nurse-led spiritual care interventions are promising in clinical settings and may improve nurses’ competence in identifying and addressing patients’ spiritual needs.